A self-organizing neural network approach for multiple traveling salesman and vehicle routing problems - Modares, A.; Somhom, S.; Enkawa, T. (International Transactions in Operational Research, 1999)
This paper addresses several algorithms based on self‐organizing neural network approach for routing problems. The algorithm for Traveling Salesman Problem is elaborated and the extension of the proposed algorithm to more complex problems namely, Multiple Traveling Salesmen and Vehicle Routing is discussed. In order to investigate the performance of the algorithms, a comprehensive empirical study has been provided. The simulations, which are conducted on standard data, evaluate the overall performance of this approach by comparing the results with the best known or the optimal solutions of the problems. The proposed algorithm shows significant advances in both qualities of the solution and computational efforts for most of the experimented data.